Bilateral keratomalacia secondary to xerophthalmia - Sapkota, Jyoti; Rana, Rachana (Nepalese Journal of Ophthalmology, 2022)
Introduction: Vitamin A deficiency leads to a wide spectrum of ocular manifestations ranging from conjunctival xerosis to corneal ulceration and perforation. Penetrating keratoplasty along with vitamin A supplementation can save the eye and useful vision. Case: A 10-year-old boy presented with decreased vision in both eyes for 3 months. Slit-lamp examination with diffuse light revealed bilateral corneal thinning with iris prolapse at inferior aspect of cornea. He underwent therapeutic penetrating keratoplasty in both eyes. Vitamin A supplementation was given as per national protocol. Till 1 year postoperatively visual acuity in RE was 6/18 and LE was pre-phthisical. Conclusion: Vitamin A deficiency is potentially a sight threatening condition, which may lead to keratomalacia and corneal perforation if neglected. Timely management with Vitamin A supplementation and penetrating keratoplasty can save the eye and vision.